Electrochemical DNA Sensor Designed Using the Pencil Graphite Electrode to Detect Listeria monocytogenes - Dincer, Emine; Kucukoglu, Nurcin; Kivanc, Merih; Sahin, Yucel (SPRINGER, 2024)
In the present work, a novel electrochemical DNA sensor was designed to detect L. monocytogenes. Two different gene fragments were selected for the sensor design. One is a 702 bp long fragment of the hlyA gene, encoding the synthesis of listeriolysin O toxin, which is unique only to pathogenic strains of L. monocytogenes and is essential for pathogenicity. The other is a 209 bp long fragment of the 16 S RNA gene found in all species of the Listeria genus. As the working electrode, the pencil graphite electrode was modified in various ways (activated or covered with polypyrrole), and six different combinations were constituted using three types of the modified working electrode and two different gene fragments. The developed system is based on differential pulse voltammetric transduction of guanine oxidation after hybridization between the selected gene fragment (38 mu g/mL) and the selected fragment-specific inosine-modified probe (1.8 mu mol/L) immobilized on a pencil graphite electrode surface. The comparison of all combinations demonstrates that the best results are obtained with the combination formed from a polypyrrole-coated pencil graphite electrode (prepared at 2 scans) and 702 bp fragment of the hlyA gene. The analysis time is less than 1 hour, and the necessary DNA concentrations for the analysis have been determined as 8.2 x 10(-11) M DNA and 2.7 x 10(-10) M DNA respectively, for the hlyA gene and 16 S RNA gene.
Keywords: Genosensors; Listeriolysin O toxin; DNA hybridization; Polypyrrole; Pencil graphite electrode; HLY GENE; BIOSENSOR; GRAPHENE; FOOD; NANOPARTICLES; OXIDE; SPP.; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology